The role of T cells in pathogenesis and protective immunity to murine malaria. - Waki, S (1992)
T-cell-mediated immunity to a virulent strain of Plasmodium berghei NK65 (Pb NK65) and to an attenuated derivative (Pb XAT) of the strain were examined in CBA mice by the administration of monoclonal antibodies against T-cell subsets or interferon-gamma (IFN-gamma). The injection of anti-CD8+ or anti-IFN-gamma delayed the mortality of mice infected with Pb NK65, although it did not affect the parasitaemia. In the late stage of PB NK65 infection, T cells, especially CD8+ T cells, were increased in number in the liver at the expense of splenic CD8+ T cells. These CD8+ T cells released IFN-gamma in culture without antigen stimulation and were thought to induce tumour necrosis factor-alpha (TNF-alpha) production by the cells in the liver. In mice infected with Pb XAT, or mice primed with Pb XAT and then challenged with Pb NK65, CD4+ T cells had a crucial role in preventing parasite growth and in protective immunity. IFN-gamma was again the key molecule in protective immunity. These results suggest that T cells stimulated with malaria antigen play important roles both in protective immunity and pathogenesis depending upon their subsets; CD8+ T cells in pathogenesis, and CD4+ T cells in protective immunity. These apparently contradictory responses may be mediated by the same cytokine, IFN-gamma.